The practical approach of the African apostolic church in contextualizing christianity in Nigeria (2012)
The question some conservatives and evangelicals often ask is whether contexualization will not lead to a scientific syncretism or a kind of christo-pagan religion? Such enquirers must not forget the history of Christianity in Africa and especially Nigeria. It must be noted that there was a church in North Africa that produced great church fathers and thinkers like Augustine, Tertullian, Athanasius and their like, but today, that church has gone into extinction. The reason given by some critics of the church is that it was never a grass root religion. It remained foreign to the people and seen as the church of aristocrats. Thus, the Islamic invasion wiped out of existence the rootless religion that once existed there. It must also be recalled that the first attempt to christianise Nigeria in the 15th century by the Portuguese and Spanish Missionaries failed because the church’s activities remained in the palaces. Historically, Henry Venn of the Church Missionary Society reeled out an epoch-making policy aimed at achieving a contextualised and indigenised Christianity in Africa. Against all odds, he contended that the African Church must be self supporting, self governing and self propagating. The first patriarch of the Methodist Church Nigeria, his Pre-eminence Bolaji also took a bold step to contextualise Methodist worship and clerical vestments. Therefore, the purpose of this paper is to evaluate the extent at which The African Apostolic Church has contextualised Christianity. This became pertinent because since its emergence in Nigeria, it has witnessed astronomic growth due to its conscious efforts at divesting itself with European garbs which identified with the western education and culture.